An electrocatalytic membrane-assisted process for hydrogen production from H2S in Black Sea: Preliminary results - Ipsakis, D.; Kraia, Tz; Marnellos, G. E.; Ouzounidou, M.; Voutetakis, S.; Dittmeyer, R.; Dubbe, A.; Haas-Santo, K.; Konsolakis, M.; Figen, H. E.; Guldal, N. O.; Baykara, S. Z. (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
The feasibility of hydrogen production by the decomposition of H2S in an electrocatalytic membrane reactor for the exploitation of H2S contained in Black Sea water is investigated. A micro-structured electrochemical membrane reactor with a proton-conducting ceramic membrane is considered for processing gaseous H2S diluted (1 vol.%) in H2O mixtures. Y-doped barium zirconate (BaZr0.83Y0.15O3-delta) is employed as solid electrolyte. Ceria supported transition metal (Co, Ni, Fe, Cu) catalysts and LaCrO3 composites are explored as anode materials and La0.6Sr0.4CO0.2Fe0.8O3-delta perovskite type oxides are used as cathode electrodes. Preliminary results concern materials preparation and characterization of the catalytic performance of anodic electrode materials. Co/CeO2 composites show excellent H2S conversion and stability performance in wet and dry atmospheres at 873-1123 K. Presence of water has a beneficial effect on the H-2 formation, in accordance with thermodynamics. The overall process starting from H2S containing sea water to H-2 generation in the membrane reactor and H2SO4 production in a sequential step is simulated and its energy balance is discussed.
Keywords: Hydrogen production; Hydrogen sulphide; Electro-catalytic membrane reactors; Proton conducting solid electrolyte; Electro-catalysis; Integrated process energy analysis; FUEL-CELL; THERMAL-DECOMPOSITION; CHEMICAL-STABILITY; SULFIDE; SULFUR; ELECTROLYTE; OZONATION; OXIDATION; KINETICS; REMOVAL; Chemistry; Electrochemistry; Energy & Fuels